Respostas
respondido por:
2
(2x-1).(2x-1)=-8(2x+1)
4x²-2x-2x+1=-16x-8
4x²-4x+1+16x+8=0
4x²+12x+9=0
Δ=b²-4ac
Δ=12²-4.4.9
Δ=144-144
Δ=0
X= -b±√Δ/ 2a
X=-12±√0 / 2.4
X=-12±0 / 8
X' e X" = -12/8 = -3/2
4x²-2x-2x+1=-16x-8
4x²-4x+1+16x+8=0
4x²+12x+9=0
Δ=b²-4ac
Δ=12²-4.4.9
Δ=144-144
Δ=0
X= -b±√Δ/ 2a
X=-12±√0 / 2.4
X=-12±0 / 8
X' e X" = -12/8 = -3/2
adriantel2012:
Tire-me uma duvida: De onde surgiu o 8?
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás